Peran Badan Permusyawaratan Desa dalam Pengawasan Dana Desa - Ade Krisdian Pratama; Badaruddin Badaruddin; Abdul Kadir (Universitas Medan Area, 2021)
This study was conducted to analyze the role of the Village Consultative Institution (BPD) in monitoring the use of Village Funds in Kuta Pinang Village, Tebing Syahbandar District, Serdang Bedagai Regency. This research uses descriptive qualitative research methods, data collection techniques by conducting literature studies and research in the field. Data analysis was performed by reducing data, presenting data and drawing conclusions. The role of BPD includes three things, namely the role in regulations, organizations / institutions and in individuals. The results showed that the role of the Village Consultative Body (BPD) of Kuta Pinang Village in the supervision of Village Funds by monitoring and auditing financial reports on the use of village funds. The follow-up of the supervision that has been carried out by the BPD which is an evaluation of the performance of the Kuta Pinang village government has also not been available so that the role of supervision has not been optimal. In addition to these aspects, the findings in this study are the obstacles faced by the BPD of Kuta Pinang Village in conducting supervision, namely the lack of community participation in village deliberations, the BPD does not understand the regulations for the use of village funds, BPD resources are still inadequate and inaccurate monitoring documentation, so that the impact on the implementation of supervision is not optimal.